1997
DOI: 10.1074/jbc.272.11.6858
|View full text |Cite
|
Sign up to set email alerts
|

Native and Multimeric Vitronectin Exhibit Similar Affinity for Heparin

Abstract: For many years, the concept that the heparin-binding sequence is sequestered within vitronectin and exposed upon denaturation of the protein has guided experimental design and interpretation of related structurefunction studies on the protein. Within the circulation, complicated networks of interactions between proteins and other macromolecules are important for maintaining stasis. An example of the complex interplay that must exist among these biomolecules is provided by the human glycoprotein, vitronectin. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 54 publications
(50 reference statements)
4
50
2
Order By: Relevance
“…The concentrations of rVN and r⌬sBVN needed to inhibit heparin activity by 50% were 0.04 and 0.2 M, respectively. The corresponding value for multimeric vitronectin was 0.16 M, consistent with previous measurements using this assay (41,50). The K app of 0.04 M for rVN was comparable to other recombinant forms of vitronectin previously expressed in the baculovirus system, which demonstrated 50% inhibition at 0.05 M (41).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The concentrations of rVN and r⌬sBVN needed to inhibit heparin activity by 50% were 0.04 and 0.2 M, respectively. The corresponding value for multimeric vitronectin was 0.16 M, consistent with previous measurements using this assay (41,50). The K app of 0.04 M for rVN was comparable to other recombinant forms of vitronectin previously expressed in the baculovirus system, which demonstrated 50% inhibition at 0.05 M (41).…”
Section: Resultssupporting
confidence: 77%
“…Binding of both the recombinant forms of vitronectin is similar to that of multimeric and much greater than that of native vitronectin, demonstrating the increased binding of the multimeric forms of vitronectin to heparin. This difference in the heparin-binding ability of monomeric and multimeric vitronectin has been attributed to the multivalent binding capacity of the multimeric form of vitronectin (50,51).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we cannot elucidate the mechanisms regulating the binding preferences, or the communication between sites from these data alone. An estimate of the average binding affinity, K 0.5 in the Hill equation, using these data gives a value of 1.5 nM, consistent with previously reported high affinity measurements for PAI-1-vitronectin binding interactions that were derived using an oversimplified 1:1 binding site model (25,31,(33)(34)(35)(36)(37). Although not equivalent to a true binding constant, this value of K 0.5 reflects a high affinity interaction that is in the range to give saturable binding of approximately nanomolar concentrations of PAI-1 under the conditions of this experiment, in which the vitronectin concentration was fixed at 0.5 nM.…”
Section: Fig 4 Sds-page Analysis Of Vitronectin and Pai-1 Effects Osupporting
confidence: 56%
“…The reported M r of circulating PAI-1⅐vitronectin complexes (19,20) is consistent with our results and raises the possibility that the complex, rather than the individual proteins, interacts with other macromolecules. Supporting this concept are studies demonstrating that vitronectin can bind PAI-1 and heparin simultaneously, indicating that PAI-1⅐vitronectin complexes can interact with other molecules (37).…”
Section: I-labeled Fibrin Clots By T-pa This Effect Is Dependent On mentioning
confidence: 68%
“…It was originally assumed that the heparin-binding sequence was encrypted in the native fold of the molecule (19), but more recent work from this laboratory has demonstrated that the heparinbinding site is fully exposed in native vitronectin (23). Confusion over the degree of exposure of sites within the conformationally labile protein had stemmed primarily from the application of varied preparation protocols that produce vitronectin forms that differ in oligomeric state.…”
mentioning
confidence: 99%